Betrothal and general damages for humiliation: an appraisal on harmonisation of Shari'ah and Civil Law - Mohd, Azizah; Hj Ibrahim, Badruddin; A. Kadir, Nadhilah (2023)
Betrothal is an agreement or a promise to marry. Both Islamic and Civil Law recognize betrothal as a significant plan before and towards a marriage contract. Both laws are also in agreement that in the event of breach of betrothal, the parties in default is liable to certain damages and compensation. Nevertheless, there are a different principle as regards to general damages for humiliation and embarrassment. This paper basically deals with betrothal and the legal effect of breach of betrothal under Islamic and Civil law. The research is a qualitative research, adopting a library research and content analysis. The research seeks to study generally on the position of betrothal under both Islamic and civil law and the effect of breach of betrothal on the parties who are at fault. This paper will further examine on items claimable as compensation under both laws including general damages for humiliation. The paper will further analyze certain points of laws on damages in breach of betrothal under both laws which are in harmony and differing to one another. Finally the paper will highlight on possibility of harmonisation between Islamic and Civil Law particularly on general damages of humiliation.